COM and .NET Interoperability - Troelsen, Andrew (Apress, 2012)
The funny thing about writing a book on COM and .NET interoperability is that one author could craft a five- to ten-page article describing the basic details that you must understand to get up and running with interop-related endeavors. At the same time, another author could write volumes of material on the exact same subject. So, you may be asking, how could this massive discrepancy between authors possibly exist?